Mass Media as Means of Initiating Community Developmental Programmes in Akoko North West Local Government Area, Ondo State, Nigeria - Gani A. Ogundahunsi; Francis O. Olaniyi (RIRAI Publisher, 2020)
The study examined the mass media as means of initiating community developmental programmes in Akoko North West Local Government Area of Ondo State, Nigeria. The study adopted descriptive research design of the survey type.The sample for the study consisted of 120 respondents in Akoko North West Local Government Area of Ondo State, Nigeria. The study raised four research questions which the data were collected through questionnaire and also tested and analyzed with descriptive statistics. The findings showed that the mass media was the best platform for mobilizing people of the community for participation and also attracts government attention to communities for developmental programmes. Based on the findings of the study, it is recommended that residents’ collaboration and empowerment form of participation is encouraged by NGOs and development agencies.